2004
DOI: 10.1897/03-242
|View full text |Cite
|
Sign up to set email alerts
|

Contaminant effects on the teleost fish thyroid

Abstract: Abstract-Numerous environmentally relevant chemicals, including polychlorinated hydrocarbons, polycyclic aromatic hydrocarbons, organochlorine pesticides, chlorinated paraffins, organophosphorous pesticides, carbamate pesticides, cyanide compounds, methyl bromide, phenols, ammonia, metals, acid loads, sex steroids, and pharmaceuticals, exert acute or chronic effects on the thyroid cascade in the approximately 40 teleost fish species tested to date. Thyroid endpoints, therefore, serve as biomarkers of exposure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
141
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 227 publications
(148 citation statements)
references
References 252 publications
(286 reference statements)
6
141
0
1
Order By: Relevance
“…Deiodinase activity is critical for regulation of tissue TH concentrations and is strongly affected by serum TH concentrations (Mol et al, 1999;Orozco and Valverde, 2005). Previous studies have shown that deiodinase activity in fish is sensitive to environmental contaminants, such as metals, polychlorinated biphenyls and pesticides (Cyr et al, 1988;Brown et al, 2004;Coimbra et al, 2005;Li et al, 2009), and they have recommended including a measure of deiodination gene expressions as sensitive biomarkers of thyroid disruption in fish upon exposure to environmental chemicals (Picard-Aitken et al, 2007;Li et al, 2009). In the present study, we found a significant increase in Dio1 gene expression, but no significant effects on Dio2 gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…Deiodinase activity is critical for regulation of tissue TH concentrations and is strongly affected by serum TH concentrations (Mol et al, 1999;Orozco and Valverde, 2005). Previous studies have shown that deiodinase activity in fish is sensitive to environmental contaminants, such as metals, polychlorinated biphenyls and pesticides (Cyr et al, 1988;Brown et al, 2004;Coimbra et al, 2005;Li et al, 2009), and they have recommended including a measure of deiodination gene expressions as sensitive biomarkers of thyroid disruption in fish upon exposure to environmental chemicals (Picard-Aitken et al, 2007;Li et al, 2009). In the present study, we found a significant increase in Dio1 gene expression, but no significant effects on Dio2 gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…Similar observations were made for carp from some sites in the lower MRB sampled in 1995 (Blazer et al, 2002). Thyroid hyperplasia in fish and other organisms has been induced by exposure to a wide array of contaminants (e.g., Patiño et al, 2003 and studies cited by Blazer et al, 2002) and, along with endpoints indicative of thyroid function and homeostasis (see review by Brown et al, 2004), may represent a potential biomarker for contaminant effects on thyroid function. However, the effects of confounding factors such as area of kidney sampled and fish age on thyroid histopathology need to be evaluated.…”
Section: Fish Health Indicatorsmentioning
confidence: 99%
“…Three PCB congeners were negatively correlated with T4, yet both T4 and T3 were positively correlated with pentachloroanisole and dieldrin (Table 6). Some studies have shown PCBs and certain pesticides may alter 5′-deiodinase activity in fish, leading to increased T3 and reduced T4 (Brar et al 2010;Brown et al 2004). As previously suggested, plasma levels of T4 and T3 may be inconsistent biomarkers of thyroid disruption in teleosts (Carr and Patiño, 2011).…”
Section: Vtg and Thyroid Parametersmentioning
confidence: 96%
“…Measures of thyrocyte height, an index of hypertrophy, did not yield statistical site differences, but values were smallest at LV (Table 4). Although the thyroid endocrine system plays a role in gonadal development and reproduction of teleosts (Cyr and Eales, 1996), the effects of thyroid endocrine disruption on reproductive fitness have been difficult to document (Brown et al, 2004;Carr and Patiño, 2011). Recent studies with zebrafish have indicated a relationship between the status of the thyroid endocrine system and gonadal sex differentiation, pubertal development, and reproduction Sharma and Patiño, 2013).…”
Section: Vtg and Thyroid Parametersmentioning
confidence: 99%